Using electrical conductivity to determine particle sedimentation status of carbon-based slurry electrodes in electrochemical energy storage systems - Monjur Mourshed; Huy Quoc Nguyen; Bahman Shabani (Materials Science for Energy Technologies, 2023)
This paper presents an experimental work conducted to understand how the dispersion stability and sedimentation state of a carbon-based slurry affect its electronic conductivity when particularly used in electrochemical energy storage applications. This work supports the possible concept of using electronic conductivity as an indicator to quantify the sedimentation status of a slurry. Carbon slurries with the concentration of 5 wt%, 10 wt%, and 15 wt% are used to conduct this experimental study. Acid-washed and steam-activated Norit particles from peat with an average size of ∼15–35 μm are mixed with distilled water to make slurry samples. In situ measurements of slurry conductivity and sedimentation are performed at both static and flowing conditions. Maximum of ∼10 % and ∼3 % increases in conductivity are found for static and flowing slurry, respectively, after over 30 min of settlement period as the results of particle sedimentation. Surface area exposure of current collectors to slurry particles is also varied to observe the relative contribution of charge transfer by supernatant and sediment layer. It is found that slurry stability diminishes with sediment formation, and static slurry is more susceptible to forming sediment.